The Role of Astrocytes in Metabolism and Neurotoxicity of the Pyrrolizidine Alkaloid Monocrotaline, the Main Toxin of Crotalaria retusa - Pitanga, Bruno P.; Nascimento, Ravena P.; Silva, Victor Diogenes A.; Costa, Silvia L. (Frontiers in Pharmacology, 2012)
The metabolic interactions and signalling between neurons and glial cells are necessary for the development and maintenance of brain functions and structures and for neuroprotection, which includes protection from chemical attack. Astrocytes are essential for cerebral detoxification and present an efficient and specific cytochrome P450 enzymatic system. Whilst Crotalaria (Fabaceae, Leguminosae) plants are used in popular medicine, they are considered toxic and can cause damage to livestock and human health problems. Studies in animals have shown cases of poisoning by plants from the genus Crotalaria, which induced damage to the central nervous system. This finding has been attributed to the toxic effects of the pyrrolizidine alkaloid (PA) monocrotaline (MCT). The involvement of P450 enzymatic systems in MCT hepatic and pulmonary metabolism and toxicity has been elucidated, but little is known about the pathways implicated in the bioactivation of these systems and the direct contribution of these systems to brain toxicity. This review will present the main toxicological aspects of the Crotalaria genus that are established in the literature and recent findings describing the mechanisms involved in the neurotoxic effects of MCT, which was extracted from C. retusa, and its interaction with neurons in isolated astrocytes.